T and B cell responses in different immunization scenarios for COVID-19: a narrative review - Piano Mortari, Eva; Ferrucci, Francesca; Zografaki, Irini; Carsetti, Rita; Pacelli, Luciano (Frontiers in Immunology, 2025)
Vaccines against COVID-19 have high efficacy and low rates of adverse events. However, none of the available vaccines provide sterilizing immunity, and reinfections remain possible. This review aims to summarize the immunological responses elicited by different immunization strategies, examining the roles of homologous and heterologous vaccination and hybrid immunity. Homologous vaccination regimens exhibit considerable variation in immune responses depending on the vaccine platform, particularly concerning antibody titers, B cell activation, and T cell responses. mRNA vaccines, such as mRNA-1273 and BNT162b2, consistently generate higher and more durable levels of neutralizing antibodies and memory B cells compared to adenovirus-based vaccines like Ad26.COV2.S and ChAdOx1. The combination of two distinct vaccine platforms, each targeting different immune pathways, seems to be more effective in promoting long-lasting B cell responses and potent T cell responses. The high heterogeneity of the available studies, the different dosing schemes, the succession of new variants, and the subjects’ immunological background do not allow for a definitive conclusion. Overall, heterologous vaccination strategies, combining sequentially viral vector and mRNA may deliver a more balanced and robust humoral and cellular immune response compared to homologous regimens. Hybrid immunity, which arises from SARS-CoV-2 infection preceded or followed by vaccination produces markedly stronger immune responses than either vaccination or infection alone. The immune response to SARS-CoV-2 variants of concern varies depending on both the vaccine platform and prior infection status. Hybrid immunity leads to a broader antibody repertoire, providing enhanced neutralization of variants of concern. Heterologous vaccination and hybrid immunity may provide further opportunities to enhance immune responses, offering broader protection and greater durability of immunity. However, from all-cause mortality, symptomatic or severe COVID, and serious adverse events at present it is not possible to infer different effects between homologous and heterologous schemes. Next-generation vaccines could involve tweaks to these designs or changes to delivery mechanisms that might improve performance.